Examining the impact of uniform manipulations on perceptions of police officers among Canadian university students. (25th November 2021) - Jenkins, Bryce; Semple, Tori; Bennell, Craig; Carter, Elizabeth; Baldwin, Simon; Blaskovits, Brittany
ABSTRACT: It is important to understand how uniforms influence public perceptions of the police. The current study utilized a randomized design in which undergraduate students at a Canadian university were exposed to a series of photographs of officers wearing different uniform configurations (i.e., special duty vs. traditional uniform, dark vs. light shirt, dishevelled vs. tidy uniform, and uniform trousers with and without a stripe). Participants rated each officer on numerous scales including: (1) the officer's personal qualities (e.g., helpfulness), (2) abilities or behaviors that the officer is likely to display (e.g., excessive force), and (3) the behavioral intentions of the participant toward the observed officer (e.g., willing to confide sensitive information to them). When controlling for general perceptions of police legitimacy, results suggest that, compared to the control conditions (i.e., normal operational uniform), introducing the uniform manipulations significantly influenced ratings on items related to community relations, professionalism, and officer safety. The current study speaks to the complicated relationship between the police appearing approachable and professional to the public, while also considering possible officer safety concerns associated with their uniform.